Studi Pelacakan Peran dan Pekerjaan Alumni Jurusan Komunikasi Penyiaran Islam Fakultas Dakwah dan Ilmu Komunikasi IAIN Padangsidimpuan - Mohd. Rafiq (Hikmah, 2019)
This study aims to describe the profile of the role of alumni from 1998 to 2018 Department of Islamic Broadcast Communication Communication IAIN Padangsidimpuan FDIK in society and the world of work; explain the suitability of alumni of the Department of Islamic Broadcast Communication Communication with alumni work; reveal the facts of the obstacles of alumni of the Islamic Broadcasting Communication Department in getting a job; explain the factors that cause the difficulty in carrying out the competence of KPI Department alumni in the community.This research is a Mixing study because it uses two approaches at once, namely qualitative and quantitative suppressors. Qualitative sword is used to analyze data based on interviews with KPI Alumni. While the quantitative approach is used to process numerical statistical data from the distribution of questionnaires to respondents of 46 people who were sampled in this study.The results showed that, firstly; the role and progress of KPI alumni in the community is very positive. Nominally have an important position in the community because they have the ability to communicate well, able to become a drafter who has many new ideas and ideas that are needed by the community. Second; KPI alumni generally work in accordance with KPI alumni profiles, namely as Dai, Public Relations Workers, although they work in many professions, but they do not leave their profession as preachers and public relations workers.